Abstract of Invited Speaker : Green Concept in Engineering Practice - Biyanto, Totok Ruki (IPTEK Journal of Proceedings Series, 2015)
In recent time, becoming green is not only a matter of compliance with regulations, however it is a matter of responding to the expectations and demands of our world, country, community, stockholders, customers, employees and competitors. These matters create tremendous pressure for companies to carry out their activities in a more environmental friendly.Being green requires the best engineering minds and commitment from the entire organization. Engineering is all  about  practicality  finding  solutions  to  improve  theconditions. Excellent understanding of the fundamental engineering  is  a  key  to  helping  industrial  activities  tobecome greener and the engineers are in an ideal position to contribute in these activities, in term of development andimplementation of technologically sound, as well as cost- effective solutions.Green initiatives create big business opportunities in the order of trillions of dollars for innovative companies and engineers,  in  this  decade.  These  business  activities  arestarted from research and development, plant design, plant construction and plant operation stage. This paper presents some ideas on how to implement the green concept in engineering  activities.  The  case  studies  application  ofgreen engineering in refinery crude preheat train and cement plant waste heat recovery generation are also presented